2020
DOI: 10.3126/jbssr.v5i2.35236
|View full text |Cite
|
Sign up to set email alerts
|

The Stock Market’s Reaction to Unanticipated Catastrophic Event

Abstract: Several factors influence the stock market; they trigger market over-or under-reactions. The paper aims to identify the effect of a major catastrophic event on stock returns. For this, daily data of stock market indices was used with a total of 210 observations and the effect of catastrophic event, Nepal Earthquake 2015, was tested using the method of event analysis for different event windows. The catastrophic event did not affect stock returns significantly and was resilient to earthquake-induced shocks. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…Furthermore, the study found a strong negative correlation between the cumulative cases, volume, and index closing value in COVID-19's first year, which supports the findings of Hamal & Gautam (2021) and shows that the COVID-19 outbreak and government policy measures had a significant and negative impact on stock market volatility, return, and overall performance in the short term. However, there was a significant positive correlation for the second year of COVID-19, which partially aligns with the findings of Karki (2020) and Dangol (2008), which found that the Nepalese Stock Market was inefficient.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Furthermore, the study found a strong negative correlation between the cumulative cases, volume, and index closing value in COVID-19's first year, which supports the findings of Hamal & Gautam (2021) and shows that the COVID-19 outbreak and government policy measures had a significant and negative impact on stock market volatility, return, and overall performance in the short term. However, there was a significant positive correlation for the second year of COVID-19, which partially aligns with the findings of Karki (2020) and Dangol (2008), which found that the Nepalese Stock Market was inefficient.…”
Section: Discussionsupporting
confidence: 86%
“…Gao et al (2021), Bora & Basistha (2021), and Chaudhary et al (2020) found that COVID-19 had a significant leverage on stock market volatility. However, research conducted in Nepal by Karki (2020), Dangol (2008), andHamal &Gautam (2021) has found that catastrophic events only have a shortterm effect on the volatility of NEPSE. Moreover, the only study on the impact of COVID-19 on stock volatility conducted by Hamal & Gautam (2021) used the Systematic Literature Review method without the use of the NEPSE data.…”
Section: Problem Statementmentioning
confidence: 99%
See 2 more Smart Citations
“…While the majority of countries depicted similar results, some countries like Pakistan did not experience a negative effect of the increase in confirmed cases and death cases but instead realized a positive effect of recovery rate on stock market (Ahmed, 2020). Such discrepancies in stock performance improvement despite the crisis period were explained by Karki (2020) by denoting the market as inefficient as such markets cannot explain investor sentiment or do not account for information in the environment.…”
Section: Discussionmentioning
confidence: 94%